SMART RECOVERY ACEH MODEL: INTEGRATING EMERGENCY EDUCATION AND MSME EMPOWERMENT FOR COMMUNITY-BASED POST-DISASTER RECOVERY - Intan Maulida; Lia Rista; Almunadiya; Raudhatinur; Rahmiatul Aula; Muhammad Multazam; Rifki (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
The flood disaster that occurred in North Aceh on November 26, 2025, significantly disrupted the social and economic conditions of affected communities, particularly in Keude Geudong Village. This study aims to examine the effectiveness of a community-based post-disaster recovery model that integrates emergency education and micro, small, and medium enterprise (MSME) empowerment. A community-based participatory approach was employed, involving two main target groups: school-aged children and MSME actors. Data were collected through observations, interviews, and program documentation, and analyzed using descriptive quantitative and qualitative methods. The results show that the social intervention successfully restored access to education, achieving over 80% participation and improving children’s learning motivation and psychosocial well-being. In the economic sector, MSMEs experienced a 40–60% increase in production capacity and a 25–35% increase in income, supported by improved financial management and digital marketing adoption. The integration of appropriate technology and continuous mentoring further enhanced program effectiveness and sustainability. This study highlights that combining social and economic interventions within a community-based framework can generate synergistic impacts and strengthen post-disaster resilience. The proposed model offers a practical and replicable approach for sustainable recovery in disaster-affected communities.